2022
DOI: 10.3390/su142012970
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Female Students Transforming Entrepreneurial Competency, Mindset, and Intention into Sustainable Entrepreneurship

Abstract: Entrepreneurship has been viewed as an opportunity for economic development and changing economic scenario in global markets. Women are viewed as a reservoir of entrepreneurial talents, so they can be growth engines in novel markets. Previous studies have considered entrepreneurship as the most effective way towards the economic empowerment of women. Female students engaged in entrepreneurial education have been addressed persistently, while what transforms them in an education process is still unclear. Consid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…For example, recently, in a sample of 215 polytechnic students in Indonesia, Mahfud et al ( 2020 ) found that entrepreneurial attitude orientation, social capital, and PC could collaboratively influence the polytechnic students' EI, and PC was found to fully mediate the impact of social capital on EI. Similarly, a study targeted 752 female students, and Chang et al ( 2022 ) indicated that an entrepreneurial mindset had a mediation effect between entrepreneurial competency and EI; in particular, without an entrepreneurial mindset, entrepreneurial competency alone cannot significantly exert effects on EI. As with other research, this finding from the present study was not conclusive; to understand this issue, more research should be added up.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recently, in a sample of 215 polytechnic students in Indonesia, Mahfud et al ( 2020 ) found that entrepreneurial attitude orientation, social capital, and PC could collaboratively influence the polytechnic students' EI, and PC was found to fully mediate the impact of social capital on EI. Similarly, a study targeted 752 female students, and Chang et al ( 2022 ) indicated that an entrepreneurial mindset had a mediation effect between entrepreneurial competency and EI; in particular, without an entrepreneurial mindset, entrepreneurial competency alone cannot significantly exert effects on EI. As with other research, this finding from the present study was not conclusive; to understand this issue, more research should be added up.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, EM has become more prevalent in discussions of entrepreneurship, as researchers examine its origins, mechanisms, and manifestations [2]. Defined as the ability to perceive, act, and mobilize in ambiguous situations [28], EM is an important factor for understanding how entrepreneurs approach their work [29].…”
Section: Entrepreneurial Mindset (Em)mentioning
confidence: 99%
“…Several studies have investigated EI directly, using various factors such as entrepreneurial motivation, need for achievement, entrepreneurship attitude, subjective norms, innovation, personality traits, entrepreneurial orientation, ECs, EM, entrepreneurial education, EMTs, organizational skills, subjective beliefs, and career opportunities [27,[59][60][61]. In Saudi Arabia, EI has been examined through university students' ECs and EM, but the roles played by EM and EMTs in mediating the relationship between ECs and EI still need further exploration [2].…”
Section: Entrepreneurial Intention (Ei)mentioning
confidence: 99%
See 2 more Smart Citations